Immunoprotective Effect of Seabuckthorn (Hippophae rhamnoides) and Glucomannan on T-2 Toxin-Induced Immunodepression in Poultry - T. Ramasamy; C. Varshneya; V. C. Katoch (Veterinary Medicine International)
The present investigation was undertaken to study the immunoprotective effect of seabuckthorn berries and glucomannan against T-2 toxin-induced immunodepression in 15-day-old chicks. T-2 toxin was produced in the laboratory by growing Fusarium sporotrichioides MTCC 2081 on wheat. T-2 toxin was fed to birds at 1 ppm level of the diet. The powdered seabuckthorn berries were added at 400 and 800 ppm levels, and glucomannan added at 1 g/kg of feed. All the treatments were continued up to 28 days. The immunoprotective effects of seabuckthorn and glucomannan were assessed by evaluating humoral immune reaction against NCD vaccine (haemagglutination test and immunoglobulin estimation), serum immunoglobulin levels, phagocytic index, and DTH reaction against DNFB between day 25 and day 28 of experiment. There was significant (P<.05) decrease in non-specific immunity in T-2 toxin-treated group as evidenced by a reduction in phagocytic index, DTH reaction, HI titer, and total serum Ig compared to the healthy control group. A significant increase (P<.05) in HI titer and total serum Ig was seen in seabuckthorn and glucomannan fed group. A significant (P<.05) increase in DTH reaction and non-specific immune response was seen in seabuckthorn and glucomannan fed birds. The present investigation revealed that the seabuckthorn alone protected the immunosuppressant action of T-2 toxin, but seabuckthorn and glucomannan in combination provided an additive protection against T-2 toxicity.